2020
DOI: 10.1186/s12944-020-01218-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid disorders in children living with overweight and obesity- large cohort study from Poland

Abstract: Background: While in the general paediatric population the presence of abnormal lipid values is estimated at 8-20%, depending on the population, accepted norms and age, it was shown that in the population of lean children the prevalence of dyslipidemia is lower than in obese children, in whom it ranges from 20 to over 40%. Until now, however, no results of similar studies on a large sample of children form a Central or Eastern European country have been published. The aim of this study was to evaluate the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
5
29
2
Order By: Relevance
“…The incidence of dyslipidemia is steadily increasing along with the incidence of obesity and metabolic syndrome. Changes in lifestyle and environment, weight gain, unhealthy diet, and lack of physical activity have caused higher rates of childhood dyslipidemia than in the past [ 14 , 34 ]. According to current guidelines, children with a family history of CVD or with risk factors such as hypertension, smoking, DM, obesity, and chronic kidney disease are screened by measuring their lipid profile after fasting for at least 8–12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of dyslipidemia is steadily increasing along with the incidence of obesity and metabolic syndrome. Changes in lifestyle and environment, weight gain, unhealthy diet, and lack of physical activity have caused higher rates of childhood dyslipidemia than in the past [ 14 , 34 ]. According to current guidelines, children with a family history of CVD or with risk factors such as hypertension, smoking, DM, obesity, and chronic kidney disease are screened by measuring their lipid profile after fasting for at least 8–12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a part of the "6-10-14 for Health" integrated weight management program for children with overweight and obesity from Gdansk, Poland, previously described. [12][13][14] Analyzed data included children aged 10-12yrs attending the interventional program in 2011-2015. Children were screened in primary schools and if overweight or obesity was diagnosed they were invited to multidisciplinary, 12-month-long program.…”
Section: Methodsmentioning
confidence: 99%
“…Childhood overweight and obesity have become a global public health concern, and numerous studies have shown that there is a distinct rise in overweight and obesity prevalence in both urban and rural regions of China ( 8 ). Childhood overweight and obesity are associated with short-term risk of cardiovascular risk factors [such as elevated blood pressure ( 9 ), adverse lipid profiles ( 10 )]. Noteworthily, there is accumulating evidence suggesting that childhood obesity tends to track into adulthood and subsequently increase the long-term risk of adult cardiovascular and metabolic diseases ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%